Trans-anastomotic tube in esophageal atresia with trachea-esophageal fistula repair: how beneficial are they? - Gupta, Pradeep; Mujalde, Vikram Singh (International Journal of Research in Medical Sciences, 2021)
Background: Congenital esophageal atresia with tracheo-esophageal fistula is a common congenital anomaly facing at our centre. There is various proposed anastomotic technique to avoid post-operative complications. In our center, feeding has been conventionally initiated after a contrast esophagogram done at the seventh day post repair. The current study tried to assess the benefits and risks of initiation of early feeding in these patients by placement of a Tran’s anastomotic feeding tube during the repair. Methods: Twenty-five patients had a trans anastomotic feeding tube inserted during trachea esophageal fistula repair and were followed up for different outcomes. Results: Twenty-five patients were operated out of which were sixteen males and nine were females. Early complications of esophageal atresia surgery such as anastomotic leak, surgical site infection, pneumonia and sepsis occur in eight patients. All the complications were managed successfully conservatively, however, one patient died due to anastomotic leak and subsequent septicemia. Conclusions: We conclude that early tube feeding is safe and does not increase risks of anastomotic leaks. It also reduces the need of total parenteral nutrition bringing down the costs of procedure in developing nations.